Rationality of Drug Administration in Patients with Diabetes Mellitus at Royal Prima Hospital Medan - Lubis, Graida Tsuraiya; Simanjuntak, Nerly Juli Pranita; Razoki (Health & Medical Sciences, 2025)
Acute and chronic diseases caused by poor lifestyle choices or genetics are becoming more common over time and do not seem to be decreasing each year.  This study aims to determine whether the treatment of type 2 diabetes mellitus patients with or without hypertension at Royal Prima Medan Hospital is appropriate.  Descriptive research methodology, namely cross-sectional data, was used in this study.  Retrospective data collection was conducted using information from medical records at one of the Royal Prima Medan University Hospitals from November 2023 to April 2024. Based on 93 medical records, the findings showed that the right drug, right indication, and right dose were all 100% rational.  Moderate drug interactions accounted for 67% of all drug interactions, major interactions 18%, and minor interactions 15%.  In conclusion, Royal Prima University Hospital in Medan had 100% rational medical data for the period November 2023-April 2024.